Let's visit the evergreen forest - Silverman,Buffy; Silverman,Buffy (Minneapolis: Lerner Publications, 2016)
Winter lasts a long time in the evergreen forest biome. The trees here stay green all year. But how do tree needles help a tree survive the winter? Read this book to find out!
Keywords: Conifers Ecology; Conifers Ecology Juvenile literature